Mentoring and Implementation of Digital Parenting Concepts for Teachers and Parents in Semarang City - Achmad Hasmy Hashona; Moh Syakur (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2025)
The development of digital technology in the era of the industrial revolution 4.0 has brought significant changes in early childhood education. However, the low digital literacy of teachers and parents creates a gap in child mentoring. This service activity aims to strengthen collaboration between RA teachers and parents in implementing the concept of healthy and educational Digital Parenting. The method used is Service Learning with the stages of needs analysis, training, and evaluation carried out in a participatory manner. Data was obtained through observation, questionnaires, and participant feedback, and then analyzed using thematic analysis techniques. The results show an increase in digital literacy, the ability to use technology creatively and safely, and the building of collaboration between schools and families in digital parenting. This program has succeeded in encouraging the application of the tricenter principle of education in facing the challenges of early childhood care in the digital era.